Analysis Movement of Unmanned Underwater Vehicle using the Inertial Measurement Unit - Mohd Aras, Mohd Shahrieel; Mohd Farriz , Md Basar; Abdul Azis, Fadilah; Fara Ashikin , Ali (2013)
In an Unmanned Underwater Vehicle (UUV), the craft's orientation, velocity, and gravitational forces are the important measurements to make sure the UUV’s navigation system can be fully operated. Most of the current UUV system uses pressure sensor to control the navigation of the craft. But the pressure sensor is not suitable to use in getting UUV’s navigation data or information. Without the information on UUV’s navigation, there are difficult to monitor the movement of UUV. This project introduces a methodology to analyze the position, velocity vector and the rotation of UUV, using a combination of accelerometer and gyroscope. This sensing unit is a combination of Accelerometer ADXL-345 sensor and Gyroscope ITG-3200 sensor called as an Inertial Measurement Unit (IMU). The measurement unit will be programmed by an Atmel microcontroller (Arduino UNO) to get the important data of the UUV’s navigation system. The real-time data of sensing unit communicated with Serial Chart and Processing software to get output graph and real-time 3D animation of UUV. From this project outcome, the movement of UUV is monitored in processing software. Hence, the navigation system of a UUV such as auto depth control, left-right movement and obstacle avoidance purpose can be improved.